An integral-momentum analysis of the laminar boundary layer along a rectangular corner. - Liongson, Leonardo Q, Ph D (Philippine Engineering Journal)
An integral momentum analysis is applied to the problem of the laminar boundary layer along a rectangular corner. It involves an assumed self-similar velocity profile defined by functions with prescribed properties. Two case examples are provided. Reasonably good agreement is obtained between the results of the present study and the available numerical solution of previous workers on the problem.